The Exploration of Bioactive Peptides that Docked to SARS-CoV-2 Spike Protein from Goats’ Milk Beta-Casein by In Silico - Widodo, Hermawan Setyo; Murti, Tridjoko Wisnu; Agus, Ali; Pertiwiningrum, Ambar (Universitas Jenderal Soedirman, 2023)
Beta-casein in milk is known to be a bioactive peptide producer because of its amino acid sequence. Bioactive peptides have prospected molecules that can adhere with SARS-CoV-2 spike protein, so they can inhibit the virus from hooking up with human cell receptor protein. The research is aimed to find any peptides from goat’s milk beta-casein that are prospective candidates as SARS-CoV-2 spike protein inhibitors. Goat’s milk beta-casein was simulated as being digested by the digestive tract. Pepsin, trypsin, and chymotrypsin enzymes cut the beta-casein amino acids sequence into small peptides. Then, their bioavailability was predicted by Lipinski’s Rules of 5 (Ro5), any most fitted peptides to the rules will be simulated to dock to SARS-CoV2 spike protein besides Curcumin as the control ligand. Peptides with the best bind activity with the spike protein will be selected as inhibitor candidates. Peptide QPK is selected as a SARS-CoV-2 inhibitor candidate because it has better affinity energy than Curcumin or other selected peptides.